Environmental Economics: An Introduction - Field, Barry C.; Field, Martha K. (New York, NY : McGraw-Hill, 2021)
"When our descendants look back at the last part of the 20th century, and now at the beginning of the 21st, we want them to be able to say: "That's when they began to take the degradation of the natural environment, with its threats to human life and the life of the planet, seriously." Furthermore, we would like them to be able to see that around this time we took serious steps to halt and reverse this process. This book is an introduction to environmental econom-ics, one way of approaching the steps that need to be taken. It's about the way human decisions affect the quality of the environment, how human values and institutions shape our demands for improvement in the quality of that envi-ronment, and, most especially, about how to design effective public policies to bring about these improvements. Problems of environmental quality are not something new; in fact, history is filled with bleak examples of environ-mental degradation, from deforestation by ancient peoples to mountains of horse manure in urban areas in the days before automobiles. But today's world is different. For one thing, many people in economically developed countries, having reached high levels of material well-being, are beginning to ask questions: What good is great material wealth if it comes at the cost of large-scale disruptions of the ecosystem by which we are nourished? More fundamental, perhaps, is the fact that with contemporary economic, demographic, and technological developments around the world, the associated environmental repercussions are becoming much more widespread and lethal. What once were localized environmental impacts, easily rectified, have now become widespread effects that may very well turn out to be irreversible"--
Includes bibliographical references and indexes.
Keywords: Environmental economics; Economic development -- Environmental aspects